Preparation and characterization of Al-12Si/ceramic composite phase change heat storage material - Zhang, Gaoqun; Duan, Dabo; Zhang, Jingcen; Hao, Junjie; Deng, Zhanfeng (Frontiers in Energy Research, 2024)
Thermal storage ceramics using metals as phase change materials (PCMs) have both high thermal conductivity and high heat storage density. However, in the process of use is very easy to occur in the metal phase change material leakage, will seriously affect the service life of the thermal storage ceramics. In this study, ceramic composite phase change heat storage materials with Al-12Si alloy as phase change material were prepared. Firstly, Al-12Si was pretreated by sol-gel method and high temperature heat treatment to obtain the pretreated Al-12Si alloy powder with dense alumina shell layer. After that, the pretreated Al-12Si alloy powder was mixed and pressed with alumina, silicon dioxide, magnesium oxide, and mullite respectively, and sintered at 1100℃, 1200℃, or 1300℃. The experimental results show that the metal phase change materials and the four ceramic materials show good chemical compatibility, and pretreated Al-12Si essentially retains its initial shape and is uniformly dispersed in the heat storage material. Among all the samples, the pretreated Al-12Si / mullite ceramic thermal storage materials with a sintering temperature of 1200°C showed the best thermal storage performance. The thermal conductivity of the samples was up to 17.94 W/(m• K). The latent heat storage value was 139.51 J/g before thermal cycling, 138.27 J/g after 100 thermal cycling, which was only decreased by 0.89%, and there was almost no alloy leakage. This study has successfully realized that the ceramic thermal storage material possesses high thermal conductivity, high thermal storage density and excellent thermal cycling performance at the same time, and provides a new method for the production and preparation of Al-12Si/ceramic heat storage materials, which has great potential for application in heat storage systems.